Is The Constitutional And Legal Recognition Of Traditional Community Laws Within The Multicultural Country Of Indonesia A Genuine Or Pseudo Recognition? - Nurjaya, I Nyoman (Constitutional Review, 2015)
Indonesia is well known amongst Southeast Asian countries for it multi- cultural identity in terms of ethnicity, religion, race and social stratification. Indonesia embodies its motto of Unity in Diversity, which refers to the culturally rich configuration of Indonesia, containing cultural capital and cultural power. However, cultural diversity also yields conflict due to inter-ethnic and inter- religious disputes that have the potential to generate social disintegration and even threaten the fragmentation of Â Indonesia as a Nation Â State. Â In the eyes Â  Â of legal anthropologists, sources of conflict are often based on discriminatory policies expressed within the Stateâs law and legislation with regard to the recognition and protection of local communities across the country, namely âadatâ communities practising traditional, customary law, known as âadatâ. Thus, State laws enacted and enforced by the Government tend to dominate and marginalise, even ignore the rights of Â the local communities, particularly regarding access Â  to and control over natural resources, which is otherwise governed by the adat law of the region. This paper attempts to offer an answer to the fundamental question of whether the 1945 Constitution recognises and protects the traditional communities and their adat laws by employing a legal anthropological approach, with the purpose of obtaining a better understanding of development of State law in a multicultural Nation and looking towards a more just and equitable Indonesian State law.